STUDY ON THE DEVELOPMENT POTENTIAL OF SHARIA HOTELS IN THE CITY OF JEMBER - Syah Riza Octavy Sandy; Hadi Jatmiko (Journal of Tourism Destination and Attraction, 2020)
The growth of the Islamic economic sector, including sharia tourism has spurred the management of sharia-based businesses becoming increasingly. Specifically in the tourism sector, it certainly cannot be separated from the accommodation business or in this study the focus is on the hotel business. This study aims to determine the potential and urgency of developing sharia-based hospitality in the city of Jember, knowing the perception of the public and tourists of the potential for the development of sharia-based hospitality. Analysis of the data used is descriptive and SWOT with a sample of 110 community respondents, and 150 tourist respondents. The results showed (1) tourists have a good perception of the development of sharia-based hotels, (2) people have a pretty good perception of the value of sharia-based hotel development, (3) the potential of the City of Jember so that it can be used as reference material for the development of sharia-based hotels including the majority of the Muslim population, community awareness and lifestyle that supports the development of sharia- hotels.